Synergistic oxygen vacancy and Zn-doping on SnO2 nanosheets for enhanced electrochemical CO2 conversion. (October 2022) - Bian, Xinxin; Liu, Bowen; Wang, Xiaolei; Chen, Zhimin; Gong, Rui; Jia, Wanqi; Song, Zichen; Meng, Huiyuan; Yin, Weibo; Ren, Zhiyu
Abstract: Defects engineering is one of the effective strategies to advance the CO2 conversion into value-added chemicals and fuels during the electrochemical process. It is noteworthy that multiple defects are often associated in the reaction process, hence how to stimulate their synergistic effect is extremely important, but still lacks in-depth understanding. Herein, SnO2 nanosheets with simultaneous oxygen vacancies and Zn dopants (Zn–Vo–SnO2 ), as a proof-of-concept study, were proposed to elucidate the synergistic effect of multiple defects on enhanced CO2 -to-C1 conversion. Zn–Vo–SnO2, which is prepared by coupling a facile hydrothermal reaction and a subsequent desulfurization, yields the C1 products at the lower applied potential, and maintains the FEC1 of about 95% at −0.80 V vs. RHE for a long-term operation. Evidences from systematic experiment and theoretical calculation corroborate that the charge redistribution caused by the oxygen vacancies and Zn-doping synergistically energize the CO2 conversion, in the term of the CO2 adsorption, the hydrogenation of CO2 and intermediates, and the thermodynamic energies of the rate-determining steps. This study has an insight into defect engineering to design advanced electrocatalysts for implementable CO2 recycling and utilization. Graphical abstract: Image 1 Highlights: The synergistic effect of oxygen-vacancy and Zn-doping lowers the kinetic and thermodynamic barrier of CO2 reduction. SnO2 with multiple effect yield a comparable C1 Faradaic efficiency (more than 95%), as well as satisfactory stability. It provides a universal and scalable avenue for coordinating multiple defects of catalysis for high-efficient conversion.